Experimental phase diagram for beryllium-magnesium aluminate nanoparticles. Issue 3 (15th February 2020) - Rogers, Brian M.; Castro, Ricardo H.R.
Abstract: An experimental phase diagram for nanoscale dimensions was constructed for BeAl2 O4 –MgAl2 O4 solid solutions in which polymorphs can be identified as a function of crystallite size (or temperature) and composition. Spinel and chrysoberyl are the main phases present in the diagram. Because nanoscale phase diagrams account for the energetic contribution of the surface of particles, the results enabled the calculation of the surface energies for spinel and chrysoberyl nanoparticles at various compositions, which showed a decrease in the average surface energy of spinel particles as the Be 2+ content increased while the average surface energy of chrysoberyl slightly increased. The energetic data suggest spinel particles incorporate Be 2+ into the structure until it reaches a saturation concentration, after which, additional Be 2+ ions segregate to the surface. Chrysoberyl particles do not readily incorporate Mg 2+, as evident by the minimal change in surface energies and the formation of spinel at relatively low Mg 2+ concentrations.